Effects of Surface Area of Titanium Dioxide Precursors on the Hydrothermal Synthesis of Barium Titanate by Dissolution-Precipitation - Ahn, Ki Ho; Lee, Young-Ho; Kim, Minsoo; Lee, Hong-shik; Youn, Yong-Suk; Kim, Jaehoon; Lee, Youn-Woo (AMER CHEMICAL SOC, 2013)
cWe have attempted to study the formation of BaTiO3 by hydrothermal synthesis and our experiments reveal the reaction by dissolution precipitation as the dominant operating mechanism. Two major formation mechanisms of BaTiO3 by hydrothemial synthesis involving either in situ transformation or dissolution precipitation have been previously proposed. However, the exact formation mechanism is yet to be clarified unambiguously. To investigate the mechanism in detail, we used Ba(OH)(2) and three types of TiO2 nanoparticles as precursors for the synthesis. The morphology of the BaTiO3 obtained was cubic (with rounded edges), regardless of the morphology of the TiO2 used, which indicated that the synthesis followed the dissolution precipitation mechanism In this mechanism, the surface area of TiO2, which affects its dissolution rate, played a critical role in determining the,crystal size of the BaTiO3 product. In this paper, we have also discussed the effects of the synthesis conditions on BaTiO3 particle formation.